2014
DOI: 10.1097/rhu.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Dual-Energy Computed Tomography for Detection of Urate Deposits in Renal Transplant Patients With Asymptomatic Hyperuricemia

Abstract: Background: An increasing role of dual-energy computed tomography (DECT) scan in tophaceous gout assessment is recognized, whereas its role in asymptomatic hyperuricemia is unknown.Objective: The objective of this study was to assess the prevalence of joint and renal monosodium urate deposits by DECT in asymptomatic hyperuricemia.Methods: Among a renal transplant population with at least 1 year of follow-up, we included 27 patients with sustained hyperuricemia and 11 with normal serum uric acid (SUA) levels. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Kimura-Hayama et al, in 2014, studied the faster tophaceous monosodium urate crystals (MSU) deposition found that the prevalence of new-onset gout-induced tacrolimus in KTxRwas 70.4%, while it was 40.7% with CyA. They scanned 351 anatomical regions in the 27 KTxR cases with HU and identified only one patient with MSU deposition in the quadriceps tendon [ 39 ]. This finding was inconsistent with what was already known about the commonest sites for tophaceous gout MSU crystals deposition were the Achilles and the peroneal tendons [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kimura-Hayama et al, in 2014, studied the faster tophaceous monosodium urate crystals (MSU) deposition found that the prevalence of new-onset gout-induced tacrolimus in KTxRwas 70.4%, while it was 40.7% with CyA. They scanned 351 anatomical regions in the 27 KTxR cases with HU and identified only one patient with MSU deposition in the quadriceps tendon [ 39 ]. This finding was inconsistent with what was already known about the commonest sites for tophaceous gout MSU crystals deposition were the Achilles and the peroneal tendons [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, while patients with long-term exposure to high sUA levels may be predisposed to having subclinical MSU crystal deposits, we were unable to examine such association given its cross-sectional study design. 9 Second, this study was based on a cohort of 46 patients with mild-to-moderately elevated levels of sUA. Although, to the best of our knowledge, this study is the largest study that evaluated DECT MSU crystal deposits among patients with asymptomatic hyperuricemia, evaluating a larger number of patients with MSU crystal deposits on DECT may further characterise factors associated with subclinical deposition of MSU crystals.…”
Section: Discussionmentioning
confidence: 99%
“…First, we may have included patients with a shorter duration of gout or a lesser degree of hyperuricemia, leading to MSU crystal deposition below the threshold of detection of DECT. The reported sensitivity of DECT for the detection of MSU deposits is proportional to the stage of gout, being 0.03-24 % in asymptomatic hyperuricemia [ 13 , 15 ], 79–80 % in patients with short-duration acute gout [ 12 , 13 ], 84 % in long-duration (≥3 years) acute gout [ 13 ] and 100 % in tophaceous gout [ 7 9 ]. The limit of detection of DECT is generally considered to be 2 mm, so microscopic tophi may be missed [ 16 ].…”
Section: Discussionmentioning
confidence: 99%